(3QSGdI aj Xf GdeLJgOs - (3GdbRhjfj, YHO GdhgGH Hf eMeO Hf Ydjs ((3HNW GdeDdas)
(3ChdgG (B:s
(3HSe Gddg(B...(3GdMeO ddg GdPj YdefG bhGYO GdOjf Gdbhje hCMcegG HeMceGJ cJGHg GdcQje hCJbfgG HGdCUhd GdYbdjI Ydi GdfgL GdeSJbje(B...s
(3BNQgG (B:s
...(3Ke Efj fXQJ Edi eG cJHJ Mjf GdeHGMKI eY HYV GdWdGH eY GdJObjb hGdJMbjb ajgG ef cd HGH aeG hLOJ NddG NGQLG Yf WQjbI GdCUMGH(B...s
(3fSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3CUhd Gdabgs